KOMPETENSI GURU ABAD KE-21 DAN STRATEGI PEMBELAJARAN MODERN: KAJIAN TEORETIS DAN PRAKTIS - Ali Maulida; Samsuddin; Novi Ayu Wulandari; Indri Machtifaliandri (Al Arsy: Journal of Education, Management and Islamic Thought, 2025)
The rapid advancement of information and communication technology (ICT) has significantly transformed the educational landscape, requiring teachers to master 21st-century competencies, including critical thinking, creativity, collaboration, and communication (4C). This study aims to examine the relationship between 21st-century teacher competencies and the implementation of modern learning strategies in digital-based education, as well as to identify challenges faced by teachers in Indonesian schools. The research adopts a literature review method by analyzing relevant national and international scholarly articles, books, and research reports related to teacher competencies, innovative learning models, and educational technology integration. The findings indicate a paradigm shift from teacher-centered instruction to student-centered learning approaches, such as Project-Based Learning and Problem-Based Learning, which emphasize active participation and higher-order thinking skills. However, the implementation of these strategies is constrained by limited teacher digital competence, insufficient professional training, and unequal ICT infrastructure across schools. The study concludes that strengthening teachers’ digital pedagogy through continuous professional development and supportive educational policies is essential to fostering effective, collaborative, and technology-enhanced learning environments in the 21st century.